PENGARUH PENEMPATAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN MARKETING EXECUTION PT BELANJA HITUNGAN DETIK - Kiki Mandasari; Eddy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
Purpose to determine the effect of placement and job satisfaction on employee performance Part Marketing Execution PT. Belanja Hitungan Detik. This research is included in the category of causal associative research using a quantitative approach. The research population amounted to 55 people, the sampling technique used a saturated sample. The research method uses simultaneous and partially linear regression analysis. The results of the study indicate that in simultaneous or partially ways, placement and job satisfaction have a positive and significant effect on the performance of employees Part Marketing Execution PT. Belanja Hitungan Detik.